Phylogeny and systematics of the tribe Thlaspideae (Brassicaceae) and the recognition of two new genera. Issue 2 (12th December 2017) - Esmailbegi, Shokouh; Al-Shehbaz, Ihsan A.; Pouch, Milan; Mandáková, Terezie; Mummenhoff, Klaus; Rahiminejad, Mohammad Reza; Mirtadzadini, Mansour; Lysak, Martin A.
Abstract: Thlaspideae is an Old World tribe of Brassicaceae centered in SW Asia. Thirty–seven of 42 species (ca. 88%) in 13 genera of the tribe were analyzed using nuclear ITS and chloroplast trnL–F markers in a family–wide context. Both single–marker and concatenated phylogenies corroborated Thlaspideae as a well–supported monophyletic clade. With the exception of polyphyletic Alliaria and Parlatoria and paraphyletic Thlaspi and Didymophysa, the remaining genera were monophyletic. Alliaria petiolata comprised diploid and hexaploid populations in two well–resolved clades. The non–weedy diploid and hexaploid populations are restricted to SW Asia, and together with diploid A. taurica (formerly P. taurica), formed a sister clade to well–resolved Sobolewskia (3 spp.) and P. rostrata (now treated as the new monospecific genus Lysakia) clades. By contrast, the European and North American weedy and invasive hexaploid A. petiolata populations clustered with the diploid P. cakiloidea. Polyphyletic Thlaspi formed two distinct clades easily distinguished morphologically, and two of its six species are segregated into the new genus Mummenhoffia. Elburzia is reduced to synonymy of Didymophysa, and the new combinations D. fenestrata, Lysakia rostrata, Mummenhoffia alliacea, and M. oliveri are proposed and a diagnostic key for determination of Thlaspideae genera is presented. Age estimations based only on calibration by the controversial fossil Thlaspi primeavum resulted in unrealistic old age estimates. Chromosome counts are reported for 16 species.